A review of soil NO transformation: Associated processes and possible physiological significance on organisms. (January 2015) - Medinets, Sergiy; Skiba, Ute; Rennenberg, Heinz; Butterbach-Bahl, Klaus
Abstract: NO emissions from soils and ecosystems are of outstanding importance for atmospheric chemistry. Here we review the current knowledge on processes involved in the formation and consumption of NO in soils, the importance of NO for the physiological functioning of different organisms, and for inter- and intra-species signaling and competition, e.g. in the rooting zone between microbes and plants. We also show that prokaryotes and eukaryotes are able to produce NO by multiple pathways and that unspecific enzymo-oxidative mechanisms of NO production are likely to occur in soils. Nitric oxide production in soils is not only linked to NO production by nitrifying and denitrifying microorganisms, but also linked to extracellular enzymes from a wide range of microorganisms. Further investigations are needed to clarify molecular mechanisms of NO production and consumption, its controlling factors, and the significance of NO as a regulator for microbial, animal and plant processes. Such process understanding is required to elucidate the importance of soils as sources (and sinks) for atmospheric NO. Highlights: Abiotic and biotic pathways of NO transformation are discussed. Interrelation between NO transformation processes is discussed. Unspecific enzymo-oxidative mechanisms of NO transformation are proposed. Physiological NO functions/effects in/for various groups of organisms are shown. Importance of bacterial NO as signaling substance for others organisms is highlighted.